The Use of Functional and Quantitative Assays to Study Glycoprotein Ib in Platelets Stored Under Various In Vitro Conditions - Taylor, M Ann; Anstee, D J (Thrombosis and Haemostasis, 1984)
There is much evidence to suggest that platelet membrane glycoprotein Ib is involved in the haemostatic function of platelets and it has been suggested that loss of this glycoprotein may occur during in vitro storage of platelet concentrates. In this study two quantitative radioimmunoassays were developed to measure the content of glycoprotein lb in platelets stored under a range of conditions used in blood banks. One assay involved the use of iodinated Maclura pomifera lectin and the other the binding of a monoclonal antibody (AN51) specific for glycoprotein lb. The results showed that there was no significant reduction in the glycoprotein Ib content of platelets under the storage conditions used. These results suggest that any loss of haemostatic effectiveness which occurs on in vitro storage of platelet concentrates is not attributable to a selective loss of glycoprotein Ib from the platelet surface.
Keywords: Human platelets; Platelet concentrates; Ristocetin-induced platelet aggregation; Monoclonal antibodies; Lectins